INFRASTRUCTURE READINESS TO SUPPORT SUSTAINABLE TOURISM DESTINATIONS IN BANGKA BELITUNG ISLANDS - Devi Valeriani; Rulyanti Susi Wardhani; Desy Yuliana Dalimunthe; Fitra Hartini; David Reeve (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Purpose: The purpose of this study was to determine how the readiness of infrastructure at tourist destinations in achieving sustainable tourism development in Bangka Belitung Islands, Indonesia. Research methods: The method used in this study is the IPA (Importance Performance Analysis) which is used to measure a person's level of satisfaction with the performance of others. The sample used in this study were 400 samples. Results and discussions: The results showed that the development of infrastructure at tourist destinations in the province of Bangka Belitung the main concern is the health facilities, security facilities, educational facilities and playing, the information center or the sale and handling of waste or garbage while the infrastructure is perceived less important and the level of satisfaction is at lower level, namely the availability of public transportation, bus stops, hotel/resort, souvenir shop/souvenirs, minimart, ATM/money changer as well as cultural and arts facilities, sports facilities, disable facilities, and lockers. Conclusion: That the development of infrastructure at district/ town is located on the main priorities and strengthening the necessary infrastructure and development in order to satisfy the future be tourist infrastructure.